2017
DOI: 10.21608/mjppf.2017.176022
|View full text |Cite
|
Sign up to set email alerts
|

Misr 1 and Misr 2: Two New, High Yielding and Rust Resistant Bread Wheat Cultivars

Abstract: Two newly bread wheat cultivars Misr 1 and Misr 2 were selected from CIMMYT wheat genotypes as resistant to stem rust specially the race Ug 99. Grain yield and rust resistance evaluation was performed through preliminary, advanced and varietal verification started in 2009/2010 through 2012/2013 growing seasons, compared to the check bread wheat cultivated cultivars. The results reveled that the grain yield of Misr 1 and Misr 2 exceeded wheat check cultivars in most of the tested locations. Generally, the new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The diagnostic PCR fragments indicate virulent TTKSK (Ug99) to Sr31 , Clement ( Sr31 ), and Brigardier ( Sr31 ) as a fragment of 350 bp. This was in agreement with what was defined in the greenhouse (TTKSK) in Egypt and other countries based on the North American nomenclature [ 7 , 24 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The diagnostic PCR fragments indicate virulent TTKSK (Ug99) to Sr31 , Clement ( Sr31 ), and Brigardier ( Sr31 ) as a fragment of 350 bp. This was in agreement with what was defined in the greenhouse (TTKSK) in Egypt and other countries based on the North American nomenclature [ 7 , 24 ].…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, we know very little regarding the presence of the Ug99 race in Egypt. Although Patpour et al [ 13 ] and Shahin et al [ 14 ] reported the Ug99 race in Egypt, some Egyptian varieties, such as Misr-1 and Misr-2, were chosen from CIMMYT wheat genotypes and tested in Uganda, Kenya, and Ethiopia, and they proved their resistance to stem rust disease, especially for this race [ 24 ]. Then, these two varieties were imported for cultivation in these countries to overcome this race (Ug99).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-one stem rust resistance genes (Sr,s) were evaluated for stem rust under field conditions during the seasons of 2021 and 2022 (Tables 1 and 2). The most resistant genes in 2021 were 13,22,26,28,35,37,40, GT, Brigardier (Sr31), PBW343 (Sr31), Sisson (Sr31+36), Chris (Sr7a, Sr12, Sr6), and FR*2/SRTT3-SRTT3, SR10, and in 2022 they were 13, 37, 40, GT, and FR*2/SRTT3-SRTT3, SR10, which achieved zero disease severity (Table 2). Through these results, it was found that there are five genes (13, 37, 40, GT, and FR*2/SRTT3-SRTT3-SR10) that had complete resistance to this disease during both seasons, and the second season was higher in disease severity than the first season.…”
Section: Evaluation Of 41 Stem Rust Resistance Genes (Srs)mentioning
confidence: 99%
“…Enzymatic and non-enzymatic components such as Catalase (CAT), ascorbate peroxidase (APX), peroxidase (POX), polyphenol oxidase (PPO), ascorbic acid, glutathione, carotenoids, and proline are very important in plants' defense system against stress conditions [23,24]. CAT, POX, and PPO up-regulation play a critical role in protecting plants from pathogen attack and scavenge ROS as well as alterations in membrane permeability as a result of either biotic or abiotic stresses [25,26]. Therefore, the purpose of this work was to use physiological, chemical, genetic, and anatomical analysis to determine cultivars' sensitivity and resistance to stem rust disease, as well as the genes responsible for resistance, related to the new physiological races.…”
Section: Introductionmentioning
confidence: 99%